Moses as a character in the Fourth Gospel. A study of ancient reading techniques, Stan Harstine : book review - Branch, Robin Gallaher (Old Testament essays, 2003)
Extracted from text ... BOOK REVIEWS , 784-800 791 Harstine, Stan 2002. Moses as a character in the Fourth Gospel. A study of ancient reading techniques. London: Continuum Sheffield Academic Press. (JSNTS 229). viii + 194 pages. Cloth. 50, 00. ISBN 0-8264-6026-7. Stan Harstine, a graduate of Baylor University, has written an interesting and well-documented investigation of the narrative use of Moses in the Gospel of John. Moses as a character in the Fourth Gospel: A study of ancient reading techniques takes a literary approach to references to Moses in John. Harstine finds that Moses is directly mentioned in seven distinct passages: 1:17, ..